Peningkatan Pemahaman Konsep Siswa dengan Menggunakan Pembelajaran Cooperative Tipe Group Investigation kelas IV SD N 2 Tepusen : Understanding Student Concepts Using Cooperative Learning Type Group Investigation Class IV SD N 2 Tepusen - Ulfah Arum Wiyati (PGSD FKIP UPR, 2022)
This research was conducted to improve the understanding of the concepts of fourth grade students of SD N Tepusen by using investigative group learning. The method used was classroom action research. The subjects of this study were fourth grade students with 19 students and carried out in 2 cycles. The data collection method used is a test question to measure students' conceptual understanding. The data analysis technique used is descriptive statistics. The average value of students in the first cycle showed 66.36 and in the second cycleis 71.81 which means the percentage of the original student passing45.45% and in the second cycle increased to 72.72%. Keywords: Learning, Group Investigation, Conceptual Understanding